TINGKAT KEANEKARAGAMAN HEWAN TROBLOBIONTS PADA EKOSISTEM GUA DI TAJUR BOGOR JAWA BARAT - Marhento, Giry; Alamsyah, Mashudi (Bioeksperimen: Jurnal Penelitian Biologi, 2020)
The purpose of this study was to determine the level of diversity of Troglobionts animals, species composition, species dominance, and uniformity in the Cave of Tajur Bogor, West Java. The variables in this study consisted of survey methods by calculating diversity, dominance, uniformity, and species composition to find out what types of animals are in the ecosystem of the cave. Based on the results of research on animal species found there were 10 species of biota belonging to 3 transects with a total of 88 species of cavernous biota. The sample in this study used the 10x10 M line transect method three times in different places. Determination of line transect measurements in this study is based on differences in the environmental zone at the outermost point or cave line which is the starting point of line transect measurement. The results of statistical calculations are obtained as follows: diversity biota index (H ') in the range of 0.4168-0.9684, the index of species composition (P) ranges between 0.2386-0.3861, the uniformity index (E) range between 0,4304-1, and the dominance of type (C) ranges between 5,2118-5,2118. Based on the calculation of diversity, composition, uniformity, and dominance of the type of biota in the area of Tajur Bogor, West Java, at the low-moderate level. Overall the types of biota found in this study were 3 transects, generally producing different amounts during the study, the total biota species found in the cave consisted of 88 individuals from 14 families and 14 species while the highest composition of biota types in transect III where of the 34 species found throughout the transect, 33 were in the second transect and the lowest was in transect I with only 21 species.